Badanie zróżnicowania zachowań konsumentów w przestrzeni europejskiej - założenia projektu badawczego pt. "Zachowania nabywców w zróżnicowanych kulturowo środowiskach europejskich" - Bartosik-Purgat, Małgorzata; Schroeder, Jerzy (Researching of Consumer's Behavior Differentiation in European Space - The Main Purposes of Research Project "Consumer Behaviors in Differentiated Cultural European Environments", 2006)
The international activity of companies is conditioned by many determinants, which are mainly results of complexity and changeability of foreign environment. Its elements belong to the economical, technological, political and legal factors. The area, which is still underestimated by Polish companies, is cultural environment.By increasing the knowledge about characteristic features of different consumers' cultures it can be minimized unpleasant surprises which are connected with differences between international соmpany's cultures and foreign consumers' cultures. Consumers' behaviors from culturally different European environments will be the main researching area in this project. The principal purpose of the project will be finding the answers following the question: if consumers from culturally different European environments are loyal clients; if they are ethnocentric; if they are cosmopolitan; if they internationalist; if they take into account COO (Country of Origin Effect) by purchasing particular products; if they make decisions individually; if their decision process is short/large, etc.There will be researched young peoples' segment, whose behaviors differ from cultural stereotypes. Besides, young people are the future market for Polish companies in the European countries. The project's results will be the crucial advice for Polish firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 250-256